Theory of Reasoned Action dan Literasi Teknologi terhadap Adaptasi Perubahan Teknologi - Setiawan, Amelia; Djajadikerta, Hamfri; Haryanto, Haryanto; Wirawan, Samuel (JSINBIS (Jurnal Sistem Informasi Bisnis), 2021)
One of the company's goals is business continuity. Companies can maintain their survival if supported by human resources who are also ready to follow the demands of changes in their environment. The COVID-19 pandemic is bringing very significant changes in human life today. This study aims to identify the influence of employee profiles and attitudes, subjective norms and information technology literacy on the willingness to adapt to the necessity of using information technology, especially during this pandemic time. This study uses the Theory of Reasoned Action approach as a theoretical basis, electronic questionnaires as a data collection method, and structural equation modeling to observe causal relationships between variables. The results of this study found that the model in this study had met the criteria for the model-fit test, and the only variable affecting employee attitudes was age. Subjective norm variables and information technology literacy have affected employees' intentions to adapt to information technology. The results of this study can be used by companies to design training programs that aim to improve information technology literacy and skills, especially for older employees.